Which equation represents the law of conservation of energy in a closed system?

KEi + PEi = KEf + PEf

PEi + PEf = KEi + KEf

KEi – KEf = PEi – PEf

KEi – PEf = PEi – KEf

Skip to content# Which equation represents the law of conservation of energy in a closed system?KEi + PEi = KEf + PEfPEi + PEf = KEi +

Physics ##
Comments (4) on “Which equation represents the law of conservation of energy in a closed system?KEi + PEi = KEf + PEfPEi + PEf = KEi +”

### Leave a Reply Cancel reply

KEi + PEi = KEf + PEf

PEi + PEf = KEi + KEf

KEi – KEf = PEi – PEf

KEi – PEf = PEi – KEf

KEi + PEi = KEf + PEf

Explanation

right on edge 2020

Hello there.

It would be KEi + PEi = KEf + PEf

Hope This Helps You!

Good Luck Studying ^-^

Option (a) is the correct answer.

Step-by-step explanation:

According to the law of conservation of energy, energy can neither be created nor it can be destroyed. It can only be transferred from one form to another.

In the given system, molecules will have both kinetic energy and potential energy.

Therefore, K.E_{i} + P.E_{i} = K.E_{f} + P.E_{f}

This equation represents that energy of molecules at initial state equals the energy of molecules at the final state, that is energy has transformed.

[tex]K_{i}+U_{g,i} = K_{f}+U_{g,f}[/tex]

Explanation:

A closed system is a system where exists energy interactions with surroundings, but not mass interactions. If we neglect any energy interactions from boundary work, heat, electricity, magnetism and nuclear phenomena and assume that process occurs at steady state and all effects from non-conservative forces can be neglected, then the equation of energy conservation is reduce to this form:

[tex]\Delta K +\Delta U_{g} = 0[/tex](1)

Where:

[tex]\Delta K[/tex] - Change in kinetic energy of the system, measured in joules.

[tex]\Delta U_{g}[/tex] - Change in gravitational potential energy of the system, measured in joules.

If we know that [tex]\Delta K=K_{i}-K_{f}[/tex] and [tex]\Delta U_{g} = U_{g,i}-U_{g,f}[/tex], then we get the following equation:

[tex]K_{i}+U_{g,i} = K_{f}+U_{g,f}[/tex](2)

Where [tex]i[/tex] and [tex]f[/tex] stands for initial and final states of each energy component.

Hence, the right answer is [tex]K_{i}+U_{g,i} = K_{f}+U_{g,f}[/tex]